Tell it again : repetitions from the archive : a thesis presented in partial fulfilment of the requirements for the Master of Fine Arts at Massey University, Wellington, New Zealand - O'Mahony, Antonia (Massey University, 2019)
‘Tell it Again’ is a project focused on the process of piecing together a community narrative of the industrial/residential suburb of Moturoa, New Plymouth from archival material, both public and private. I have used traditional hand-based printmaking processes because they are slow, contemplative and repetitive and I equate this with life itself as process. The seemingly ordinary repetitions in daily life that neverendingly come and go and appear to amount to little are represented here in the test poofs, the trials and errors along the way to the finished piece, of the etchings, woodcuts, monoprints and plate lithographs. However, just as with the many small repetitions and labours of making an etching or woodcut, it is on reflection that the stories become the quiet background of community and place or the lovingly crafted print.
Figures are re-used with permission.
Keywords: 360602 Fine arts